2019
DOI: 10.1177/0081246319838104
|View full text |Cite
|
Sign up to set email alerts
|

Behaviour planning and inhibitory control in Sepedi-speaking primary school children with attention-deficit/hyperactivity disorder

Abstract: Attention-deficit hyperactivity disorder is one of the most common disorders that can occur in children. The symptoms are thought to result from a deficit in executive functions. This study investigated whether children with attention-deficit hyperactivity disorder subtypes differed in behavioural planning and response inhibition, two of the domains of executive functioning, from a control group without attention-deficit hyperactivity disorder symptoms. Furthermore, it examined whether the three attention-defi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…The findings were consistent with the study conducted by Sarkis et al 54 who found that the ADHD-C subtype performed significantly worse than the non-ADHD groups on the TOL. Similarly, Pila-Nemutandani and Meyer, 20 Schmitz et al, 21 Mokobane et al 22 and Solanto et al 55 noticed that children with the ADHD-C presentations were deficient in behavioural planning and that they faced more difficulties when compared to both the ADHD-HI and ADHD-PI presentations and a control group of non-ADHD children. Saydam et al 56 also found that ADHD-C presentations had impaired planning strategies compared to the ADHD-PI presentation.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The findings were consistent with the study conducted by Sarkis et al 54 who found that the ADHD-C subtype performed significantly worse than the non-ADHD groups on the TOL. Similarly, Pila-Nemutandani and Meyer, 20 Schmitz et al, 21 Mokobane et al 22 and Solanto et al 55 noticed that children with the ADHD-C presentations were deficient in behavioural planning and that they faced more difficulties when compared to both the ADHD-HI and ADHD-PI presentations and a control group of non-ADHD children. Saydam et al 56 also found that ADHD-C presentations had impaired planning strategies compared to the ADHD-PI presentation.…”
Section: Discussionmentioning
confidence: 95%
“…Pila-Nemutandani and Meyer. 20 , Schmitz et al 21 and Mokobane et al 22 noticed that children with the combined (ADHD-C) presentation were highly deficient in behavioural planning and faced more difficulties when compared to both the predominantly hyperactive-impulsive (ADHD-HI) and predominantly inattentive (ADHD-PI) presentations and neurotypically children. However, a study by Geurts et al 23 showed no deficiencies in children with ADHD and normal controls with regard to planning.…”
Section: Introductionmentioning
confidence: 99%
“…These 18 items are similar to those in DSM-5 (Doernberg & Hollander, 2016). The study employed the DBD since it is normed for the participants (Meyer et al, 2004) and found to be valid and reliable by other studies (Mokobane et al, 2020; Pila-Nemutandani et al, 2018). Respondents were asked to rate the behaviour of the child on a four-point scale: not at all (0), just a little (1), pretty much (2), and very much (3).…”
Section: Methodsmentioning
confidence: 99%
“…The dependent variables for this task were the number of consecutive sooner-smaller and larger-later choices, which are indicators of the tolerance to forgo more immediate reinforcement in favour of a longer term reward (Dougherty et al, 2005). Validity and reliability for the TCIP have been established (Dougherty et al, 2005; Mokobane et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation